STEM Learning to Improve Problem Solving Ability on the Topic of Environmental Education - Rita Istiana; Desti Herawati; Farah Herniningtyas; Ilmi Zajuli Ichsan; Ahmad Ali (Postgraduate, University of Mataram, 2023)
STEM learning is a new innovation in 21st century education. The ability to solve problems is important for students to learn to be able to solve environmental problems. The purpose of this study is to measure the effect of STEM on the ability to solve problems on the topic of environmental change. The method used in this research is Quasi Experiment. The sample used in this study was students at high school (SMAN) 4 Cibinong, Bogor Regency. The results of this study indicate that the instrument is valid and reliable. The results of the hypothesis test show that t-count > t-table which can be interpreted that the score there is an effect of lesson study-based Science, Technology, Engineering, and Mathematics (STEM) learning on students' problem-solving abilities on Environmental Change topic. Environmental Education plays an important role in shaping students' problem-solving skills. STEM-based learning in this case must prioritize solving environmental problems that are integrated with environmental education. The conclusion from this study is that STEM learning has an impact on students' problem-solving abilities